Influence of Wood Density on Backwater Rise due to Wood Accumulations - MALLQUI, REBECA; Claros , Erick; Cabrera , Juan (Journal of Coastal and Hydraulic Structures, 2025)
The presence of wood accumulations in rivers can trigger the blockage of natural or artificial hydraulic infrastructures, especially in Amazonian rivers, causing backwater effects or variations in geomorphology. One of the factors affecting the backwater rise is the arrangement of logs in the accumulations, which depends on their buoyancy and can alter the compactness of the accumulation. In turn, the buoyancy of the wood depends on its density, which can take values from 250 kg/m3 to values greater than 1000 kg/m3, depending on the tree species, the state of decomposition and the moisture content. This research article summarizes the results of the study of the effect of wood density on backwater rise and shape of wood accumulation based on simulations in an experimental flume at variable flow rates and bed slopes. The backwater rise was generated by using a rack and to simulate the logs, artificial logs with different densities were used. The results of the reproducibility tests showed a mean relative standard error of 3.74% in the measurements of the relative backwater rise. The main findings indicate that the backwater effect increases with the density of wood logs, in that sense, a variation in the equation for the estimation of backwater rise is proposed (Schalko et al., 2019a) including density as a variable. On the other hand, it was observed that the compactness of the wood accumulations increased with the density of the wood logs, i.e., the accumulations were longer and with lower height when they were composed of lighter logs and vice versa.